Bahrain as the area of Saudi-Iranian rivalry in the second decade of the 21st century - Czornik, Katarzyna (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: Bahrain as the area of Saudi-Iranian rivalry in the second decade of the 21st century Despite Bahrain’s small size, the country’s inner political and religious configuration of powers as well as its geopolitical layout make it an area of special interest. At the same time, the existence of the above circumstances contributes to the perception of Bahrain as a field of rivalry, or even a proxy war, as was the case during the Arab Spring of 2011, between two key actors in the Persian Gulf, Saudi Arabia and the Islamic Republic of Iran. One of the factors which influence the importance of Bahrain’s position in the region is the fact that for decades the country has been ruled by a more influential Sunni minority, whereas Shia Bahrainis, who constitute majority of the population, are permanently discriminated by the government in Manama. Other factors are Bahrain’s territorial closeness to Saudi Arabia’s Eastern Province, a strategic region rich in oil deposits, inhabited by Shiites, and its territorial closeness to Shia Iran, which supports Bahraini Shiites, who are thereby considered a threat to the integrity of the Kingdom of Saudi Arabia. Key words: the Kingdom of Saudi Arabia, Bahrain, the United States, the Arab Spring, proxy war Abstrakt: Bahrajn jako obszar rywalizacji saudyjsko‑irańskiej w drugiej dekadzie XXI wieku Bahrajn, mimo iż jest państwem o niewielkich rozmiarach, to jednak ze względu na specyfikę wewnętrznego układu sił religijno‑politycznych oraz położenie geopolityczne stanowi obszar szczególnego zainteresowania, a nawet pole rywalizacji, czy też wojny zastępczej (proxy war) — jak w okresie Arabskiej Wiosny w 2011 roku — pomiędzy dwoma kluczowymi aktorami w subregionie Zatoki Perskiej — Arabią Saudyjską i Islamską Republiką Iranu. Wśród czynników, które w tej materii wpływają na ważkość Bahrajnu jest fakt, że państwem tym od dziesięcioleci rządzi sunnicka mniejszość, podczas gdy kraj w zdecydowanej większości zamieszkują szyici permanentnie dyskryminowani przez władze w Manamie. Drugi czynnik to bliskość terytorialna Arabii Saudyjskiej, której strategiczną, bogatą w zasoby złóż ropy naftowej Prowincję Wschodnią zamieszkują szyici, oraz Iranu wspierającego szyitów w Bahrajnie, którzy tym samym stanowią zagrożenie dla integralności terytorialnej Królestwa Arabii Saudyjskiej. Słowa kluczowe: Arabia Saudyjska, Bahrajn, Stany Zjednoczone, Arabska Wiosna, wojna zastępcza (proxy war)